(untitled) (Revista de Estudos da Linguagem, 2024)
The Brazilian second-round presidential debate, held on 10/28/22, reverberated a lot on Twitter/X, particularly due to the episodes of verbal attacks among candidates. The aim of this paper is to investigate the users’ reactions to the verbal conduct of the candidates to verify whether/how these reactions can be characterized as instances of impoliteness metadiscourse. We also aim to explore whether/how the metadiscourse can be seen as an analytical tool for impoliteness studies, especially from the point of view of the speaker’s perception of impoliteness (first-order impoliteness). The data were extracted from the most frequent hashtags on the platform on the day of the debate and were analyzed using a mixed approach, in which verbal, visual, and typographic elements are considered (Unger et al., 2016). The results show that users negatively evaluated the verbal behavior of the candidates and reacted to impoliteness by reciprocating it in kind. The occurrence of attempted online shaming, targeting the candidates, their supporters, and other public figures such as journalistic and members of the judiciary, also suggests the establishment of a process of normalization of impolite shameless language, attested mainly through swear words and negative assertions, as well as the accumulation of various symbolic resources, typical of the digital medium.